2014
DOI: 10.1111/papt.12035
|View full text |Cite
|
Sign up to set email alerts
|

Trauma in relation to psychosis and hospital experiences: The role of past trauma and attachment

Abstract: 30% of patients met criteria for psychosis- or hospital-related PTSD. Severity of psychosis was associated with PTSD symptoms. Anxiety in attachment relationships was positively correlated with PTSD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 44 publications
0
35
0
2
Order By: Relevance
“…Some patients still remembered their traumatic experiences (coercive treatments – in other words restraint, seclusion, and forced medication) and criticized the personnel for their judgmental attitudes, stigmatization, and labeling. The findings of the present study are consistent with those of Berry, Ford, Jellicoe‐Jones, and Haddock (), who also found that this group may be particularly vulnerable to psychosis‐related and hospital‐related posttraumatic stress disorder. Williams et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients still remembered their traumatic experiences (coercive treatments – in other words restraint, seclusion, and forced medication) and criticized the personnel for their judgmental attitudes, stigmatization, and labeling. The findings of the present study are consistent with those of Berry, Ford, Jellicoe‐Jones, and Haddock (), who also found that this group may be particularly vulnerable to psychosis‐related and hospital‐related posttraumatic stress disorder. Williams et al.…”
Section: Discussionmentioning
confidence: 99%
“…See table 1 for characteristics of included studies (Additional le 2). Four studies were based in the UK (23)(24)(25)(26), one in Australia (27), and one in Tunisia (28). Half (n = 3) were in early intervention in psychosis (EIP) services (23,26,27).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One was in secure wards with current inpatients (25) where it was likely the participants were mixed in terms of numbers of episodes and length since onset. One study utilised a sample of outpatients participating in a clinical trial (24), where all participants had co-morbid substance use disorder.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that children and adolescents struggling with psychosis are treated in the least restrictive environment with as much predictability and support as possible in order to reduce the likelihood of environmental stressors exacerbating the child's symptomatology [17]. The degree of family support for the psychotic child is essential in being able to maximize treatment benefits in the least restrictive environment.…”
Section: Need For Research On Psychotherapy and Supportive Interventionsmentioning
confidence: 99%